Atomic Layer Deposited Aluminum Oxide for Interface Passivation of Cu2ZnSn(S, Se)4 Thin‐Film Solar Cells. Issue 12 (26th April 2016) - Lee, Yun Seog; Gershon, Talia; Todorov, Teodor K.; Wang, Wei; Winkler, Mark T.; Hopstaken, Marinus; Gunawan, Oki; Kim, Jeehwan
Abstract : Nanometer‐scale‐thick Al2 O3 thin films grown by atomic layer deposition are implemented as an effective interface‐passivation strategy for improving Cu2 ZnSn(S, Se)4 ‐based thin‐film solar cell device performance. Photoluminescence characterization indicates that the enhancement originates from improved interface quality of the solar cell devices.